SPICES; Their cultivation and Post- Harest Management - S.N. Das; S.N. Das (Udaipur Agrotech Publishing Academy, 2007)
This Book will definitely fulfil the cherished dream of aspirants like studets, researchers, farmers and the enterpreneurs having interest in spices.
Spice Cultivation post- Harvest Management
Keywords: Spice; Cultivation; post- Harvest Management